Transformation of the Environment: Influence of “Urban Reagents.” German and Russian Case Studies. - Reshetnikova, Tatiana (My University, 2021)
An urban regeneration manifests itself through urban objects operating as change agents. The entailed diverse effects on the surroundings demonstrate experimental origin - an experiment as a preplanned but unpredictable method. An understanding of influences and features of urban objects requires scrutiny due to a high potential of the elements to force an alteration and reactions. This thesis explores the transformation of the milieu and mechanisms of this transformation.
Keywords: Stadterneuerung; Stadtentwicklung; Stadtbild; Stadtbildveränderung; Stadtbaukunst; Standortattraktivität; Aufwertung; Urbanität; Fallbeispiel; Internationaler Vergleich; Bilbao-Effekt